Hubungan antara Rasio Panjang Katup Mitral Posterior-Anterior dan Derajat Keparahan Stenosis Mitral Rematik - Citra Kiki Krevani; Mefri Yanni; Yerizal Karani; Masrul Syafri (Jurnal Kardiologi Indonesia, 2017)
Background: Rheumatic mitral stenosis (RMS) is the cause of mitral valve disease commonly found in developing countries. Determining severity of RMS is very important, related with prognosis and management of the disease. Current echocardiography methods have advantages and disadvantages in determining the severity of RMS. Posterior to anterior mitral valve leaflets length ratio (PMVL/ AMVL ratio) was proposed to be one of the semi-quantitative measurement which offered a simple, easy and accurate method in determining the severity of RMS. The aim of this study was to see the association of posterior to anterior mitral valve leaflets length ratio with severity of rheumatic mitral stenosis.Methods: This was a cross-sectional descriptive analytic study. The subjects were all patients with rheumatic mitral stenosis who underwent echocardiography examination to measure the PMVL/AMVL ratio as well as determining the severity based on mitral valve area (MVA) planimetry. One-way ANOVA analytic test was used to assess the association of ratio PMVL/AMVL and severity of the RMS.Results: Of 71 patients included in this study, there were 19 mild RMS, 19 moderate RMS and 33 severe RMS patients. Majority of the subjects were female with age range from 38 to 43 years and have atrial fibrillation. From echocardiography examination, the mean EF +/- 55% with increased LAVI and SPAP according to the severity of the RMS (LAVI; 44±1.3 vs. 55±1.5 vs. 74±1.7 ml/m2 SPAP; 29±1.2 vs. 46±9.0 vs. 68±1.4 mmHg). There was a significant difference in the length of PMVL in mild, moderate and severe RMS (28±5.6 vs. 22±4.0 vs. 17±5.2 mm; p<0.001), but no significant difference in the length of AMVL (33±5.5 vs 33±5.4 vs 32±5.1mm; p=0.93) respectively. The PMVL/AMVL ratio had statistically significant association with severity of RMS (p<0.001).Conclusion: The PMVL/AMVL ratio is significantly associated with severity of RMS.